PENGARUH PENGETAHUAN DAN RELIGIUSITAS SISWA TERHADAP MINAT MENABUNG DI BANK MINI SYARIAH SMK BUSTANUL FALAH BANYUWANGI - Yeni rokhilawati; Rani Safitri (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2022)
Bank Mini Syariah SMK Bustanul Falah Is One of the Sharia Banks in SMK Bustanul Falah Banyuwangi and Which cooperates with Bank Syariah Indonesia which is usually referred to by the term (BSI), which operates with sharia principles that have a vision and mission that is to become a Sharia Bank to be the choice with the best service for customers, forming professional and trusted human resources. The main problem faced by Bank Mini Syariah SMK Bustanul Falah about the factors of knowledge and religuity of students towards saving interest. Because the interest in saving students is very little and that affects the limitations of knowledge such as performance, benefits, procedures and factors that affect students' interest in using Islamic Mini Bank products either directly or indirectly, namely the existence of religious factors or religion contained in students and students, Therefore religiosity is a spiritual value of a person in practicing the religious sharia that he believes in its use. This research includes a type of Quantitaf research where the quantitative type is a type of research in the form of numbers to test a hypothesis. The population in this study is students and students of Bustanul Falah Banyuwangi Vocational School. Using Purposive Sampling techniques, 86 students were sampled. While the data collected using questionnaires with a likert scale. Hypothesis testing is carried out by multiple linear regression analysis. The results showed that Knowledge had a positive effect on saving interest in The Mini Bank of SmK Bustanul falah, because this was obtained from the calculation of Test T, namely the value of t counting > t table (2,996 > 1,662). So H0 was rejected and Ha was accepted, so it can be concluded that knowledge affects the interest in saving in the Bank Mini sharia SMK Bustanul falah, Because this is obtained from the calculation of Test T, namely the value of t count > t table (5,418 > 1,662). So H0 was rejected and Ha was accepted, so it can be concluded that Religuity affects saving interest. So it can be concluded that knowledge and religiosity together have a significant influence on saving interest. So, when the Islamic Mini Bank will increase interest in saving, both variables both knowledge and religuity must be equally considered to achieve the desired goal. Because both have their own influence on saving interest in BankMini Syariah SMK Bustanul Falah Banyuwangi.